DIY in the DNA: Macro Context and National Myth as Enduring Advertising Discourse - Desmarais, Fabrice (HERMES - Journal of Language and Communication in Business, 2017)
This study shows how national contexts recurrently foreground specific myths in advertising to increase consumers’ ‘knowledge’ of the positioning of brands and their ‘liking’ of these brands. From an extended sample of New Zealand television commercials, the research isolates the theme of ‘Kiwi Ingenuity’ as an important tool to advertise a wide variety of brands. At a micro level the study illustrates how hyperbolic characterisation works to attach emotional meanings to brands and products, in particular how ingenious characters are used as hyperbolic cultural signs. The study situates these micro representation strategies in their macro cultural context, arguing that the mechanics of national myths in advertising needs to be understood within the geopolitical context.